Palm olein emulsions potential vehicles for drug delivery - Mohd Nawi, Mohamed Sufian; Ahmad, Kausar (IIUM Press, International Islamic University Malaysia, 2017)
Palm olein emulsions were produced using the combinations of Span® and Tween® surfactants by mechanical homogenisation. Effects of the types of surfactants, concentrations, effective HLB and the types of viscosity modifiers and concentrations on the characteristics of the emulsions were investigated. With palm olein content of 20% (w/w), stable oil droplets were produced at HLB values ranging from 8.5 to 11.0. Optimal concentrations of surfactants ranged from 25 to 30% (w/w to oil) depending on the types of the Span®/Tween® mixtures. Among the viscosity modifiers used, Carbopol®940 was the most effective. Suitable concentrations of Carbopol®940 for the emulsions prepared with Span®20/Tween®20 ranged from 0.1 to 0.3% (w/w). Beyond this concentration, destabilisation of emulsion due to at least depletion of water molecules could have occurred as a result of competitive hydration between Carbopol®940 and the surfactants. The emulsions produced exhibited viscoelastic and pseudoplastic behaviour, with yield value ranging from 0.1 to 35.2 Pa. Depending on the concentration of Carbopol®940 and within the linear viscoelastic region, the emulsions were elastic in nature as shown by domination of storage modulus (G’) over the loss modulus (G”) and with tan δ < 1 in the frequency range of 0.01 to 10 Hz. These favourable rheological properties were induced by the formation of three-dimensional network of Carbopol®940 molecules in the continuous aqueous phase, which also entrapped the oil droplets and thus increased the stability of the emulsion